การสังเคราะห์การจัดการศึกษาขั้นพื้นฐานบนพื้นที่สูงและทุรกันดาร - มโนการณ์, มนต์นภัส (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบันของการจัดการศึกษาขั้นพื้นฐานบนพื้นที่สูงและทุรกันดาร 2) สังเคราะห์การจัดการศึกษาของสถานศึกษาที่มีวิธีปฏิบัติที่ดี และ 3) จัดทาข้อเสนอนโยบายต่อการจัดการศึกษาขั้นพื้นฐานบนพื้นที่สูงและทุรกันดาร โดยอาศัยการวิจัยเชิงคุณภาพ ได้แก่ การศึกษาข้อมูลเอกสาร การสนทนากลุ่ม การสัมภาษณ์ผู้ให้ข้อมูลสาคัญร่วมกับการสังเกตแบบมีส่วนร่วม ตรวจสอบความเชื่อมั่นของข้อมูลที่ได้ด้วยการใช้เทคนิคสามเส้า ผลการวิจัยพบว่า 1) สภาพปัจจุบันของการจัดการศึกษาขั้นพื้นฐานบนพื้นที่สูงและทุรกันดาร ปัญหาการจัดการศึกษามีความยากลาบาก ซับซ้อนในการบริหารจัดการ ก่อให้เกิดความเหลื่อมล้าในโอกาส คุณภาพของนักเรียนและประสิทธิภาพของการจัดการศึกษา 2) ผลการสังเคราะห์การจัดการศึกษา ขั้นพื้นฐานบนพื้นที่สูงและทุรกันดารของสถานศึกษาที่มีวิธีปฏิบัติที่ดี ประกอบด้วย (1) บ้านพักนอน (2) ห้องเรียนเคลื่อนที่ (3) หนึ่งโรงเรียน สามระบบ (4) เทคโนโลยีทางไกล (5) ทวิภาษา และ (6) ส่งเสริมอาชีพและทักษะชีวิต 3) ข้อเสนอนโยบายต่อการจัดการศึกษาขั้นพื้นฐานบนพื้นที่สูงและทุรกันดาร ควรมียุทธศาสตร์การจัดการศึกษา ที่สอดคล้องกับสภาพปัญหา มีระบบการติดตามและประเมินผลที่เหมาะสมกับบริบท พัฒนาผู้บริหารและครู ให้เข้าใจเข้าถึงการเรียนรู้ข้ามวัฒนธรรมคาสาคัญ : การจัดการศึกษาขั้นพื้นฐาน, บนพื้นที่สูงและทุรกันดาร ABSTRACT This study examines educational management for schools in highland and rural areas. The purposes of the research were 1) to explore the current situations of basic educational management for schools in highland and rural areas. 2) to synthesize good practice for the educational management of those schools, and 3) to propose the policy recommendations for basic educational management for highland and rural schools. Based on qualitative research approach, this study conducted literature review, focus group, in-dept interviews with school principals, teachers, and executive administrators, and participant observations. The triangulation technique was employed to validate the trustworthiness of the analysis. The research findings indicated that:1) the current situations of basic educational management for highland and rural areas confronted difficulties and complexities in educational problem management. Those obstacles led to inequality in educational opportunity and quality of students and low achievement of educational management; 2) good practice of educational management comprised of (1) dormitory (2) mobile classroom (3) 1 school with 3 systems (4) distance learning technologies (5) bilingual education (6) a program for developing life and career skills; and 3) the policy recommendations are as follows: educational strategies for managing highland and rural schools need to be responsive to local contexts and challenges, the monitoring and evaluation systems need to suit local settings and circumstances, and school administrators and teachers should be encouraged to gain cross-cultural capabilities.Keywords : Basic Educational Management, Highland and Rural Area